Role-Accumulation and Mental Health across the Life Course - Mize, Trenton D.; Kincaid, Reilly (American Sociological Review, 2025)
Decades of research shows that holding and maintaining multiple social roles leads to better mental health and well-being overall, but role-accumulation theory has not proposed or considered whether effects vary at different stages in the life course. Rather, the current theory assumes that social roles’ positive influence on mental health should be similar at all ages. In addition, extant work suggests that accumulating roles that are more voluntary than obligatory is the best strategy for mental health, regardless of age. In contrast, socioemotional selectivity theory suggests that in later life, adults tend to reduce their number of social roles, especially voluntary ones, as a strategy to maximize mental health. Using 21 waves/years of longitudinal data on Australian adults, we examine the effect of role-accumulation across the entire adult life course. Fixed-effects models show that the types of roles matter, with obligatory role-accumulation associated with better mental health at most ages, but not in late adulthood. In contrast, voluntary role-accumulation is beneficial at all ages, and especially for the mental health of older adults. The findings mostly support role-accumulation theory’s predictions and highlight the importance of voluntary roles for lifelong well-being. Our results suggest that creating more voluntary role opportunities that are accessible to all ages can benefit older individuals, communities, and population health more broadly.